CONSISTENCY OF SUZUKI–TSUCHIHASHI AND RENAUD METHODS IN DETERMINING DOMINANT LIP PRINT PATTERNS IN MALES AND FEMALES - Swastirani, Astika; Rahmayati, Nabilah Shafiyyah; Fidya, Fidya; Zahra, Aisya Safira (FKG ULM, 2026)
Introduction: Forensic odontology is a branch of dentistry that focuses on the resolution of forensic cases. This discipline encompasses identifying personal information, including age, race, and gender. One of the methods utilized is lip print analysis. Objective: To determine the consistency of Suzuki-Tsuchihashi and Renaud methods in determining dominant lip print patterns in males and females. Methods: This study employs a cross-sectional design with an observational approach, involving 100 respondents (50 males and 50 females) aged 18–25 years selected using quota sampling. Lip print patterns were classified using the Suzuki–Tsuchihashi and Renaud methods, and the data were analyzed to determine the consistency between Suzuki-Tsuchihashi and Renaud methods. Results: The Cohen’s Kappa analysis showed level of consistency in males is fair (κ = 0.230; p = 0.302) and moderate in females (κ = 0.422; p = 0.531). In both groups, p-values greater than 0.05 indicate no statistically significant difference between the Suzuki–Tsuchihashi and Renaud methods. Conclusion: There is no statistically significant difference between the Suzuki-Tsuchihashi and Renaud methods. However, both methods demonstrate a fair to moderate of level of consistency in classifying dominant lip print patterns in males and females. Keywords: Forensic Odontology, Gender Identification, Lip Print, Renaud Method, Suzuki-Tsuchihashi Method